Kebijakan Merdeka Belajar dan Implikasinya terhadap Pengembangan Desain Evaluasi Pembelajaran Pendidikan Agama Islam - Arifin, Syamsul; Abidin, Nurul; Anshori, Fauzan Al (Universitas Pesantren Tinggi Darul 'Ulum, 2021)
This article was written to examine the policy form of the Republic of Indonesiaâ€™s Minister of Education and Culture and its development toward the evaluation of Islamic religious education (PAI) learning. This article was written using a qualitative research method with a literature study approach. Data for the literature study were gathered through a process of scrutiny, analysis, and presentation of findings. According to the results of the literature review, the Ministry of Education and Cultureâ€™s, Nadiem Makarim, policy is known as the â€œFreedom of Learningâ€ policy. This policy addresses four issues: national standard school exams (USBN) developed by each school; changes to the national exam (UN) to a minimum competency assessment and character survey; educatorsâ€™ freedom to design lesson plans (RPP); and flexibility in new student admissions regulations (PPSB). â€œMerdeka Belajarâ€ is distinguished by its creativity, learning orientation toward problem solving, needs-based learning, and integration into the workplace, as well as a comprehensive assessment system. This has an impact on the need for PAI learning evaluation development. This article concludes that evaluation evaluation is based on the purpose of human birth as â€˜abdun and caliph; PAI learning evaluation includes aspects of â€˜aqliya, bÄá¹iniya, and â€˜amaliya; and PAI learning evaluation is carried out to balance the power of thought, dhikr, and charity.